Food choice of the tonkin snub-nosed monkey Rhinopithecus avunculus (Dollman, 1912) in Khau Ca species and habitat conservation, Ha Giang province - Lan Anh, Nguyen Thi; Dang, Nguyen Xuan; Huan, Nguyen Xuan; Duc, Nguyen Anh (Academia Journal of Biology, 2014)
It is the first time, the content of nutrients (protein, lipid, carbohydrate, ascorbic acid and mineral); anti-nutritional factors (total phenol, tannin); and metabolizable energy in plant parts which the Tonkin Snub-Nosed Monkey (TSNM) consumes and doesn’t consume have been analyzed and compared. The study results show that the food choice of TSNM follows model “avoidance or regulation of plant secondary metabolites", model “limitations of dietary fibre" in five main primate nutritional ecology models and "optimal foraging theory”. R. avunculus doesn’t choose to eat leaves of the dominant plant species at Khau Ca Species and Habitat Conservation because leaves have high total phenol, tannin content. R. avunculus chooses to eat leaves of the plant species that have high water, lipid, protein, nonfibrous carbohydrates, ash, metabolizable energy and low fiber, total phenol, tannin contents. R. avunculus chooses to eat petiole, which is not matched with the “optimal foraging theory” because the CP, ADF and CP/ADF ratio in petiole are lower than lamina; total phenol content is low (in accordance with model “avoidance or regulation of plant secondary metabolites”) and ash content is higher than lamina. R. avunculus doesn’t choose to eat lamina and mature leaves that have high ascorbic acid content. Water has highest influence to selection of leaves, petiole of TSNM, then follow nonfibrous carbohydrates, fiber and metabolizable energy.